KARAKTERISASI MIKROKAPSUL MINYAK ATSIRI JAHE DAN OLEORESIN AMPAS JAHE (Zingiber officinale var. Rubrum) DENGAN PENYALUT MALTODEKSTRIN - , fatchul anam nurlaili, Prof.Dr.Ir.E.Purnama Darmadji, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Indonesian ginger farmers usually extract ginger essential oil by distillation. Pulp was remained after the distillation process which is then dried and directly used as fuel distillation furnace. In fact, pulps still contain oleoresin which can be extracted further. Therefore, extraction of pulp ginger oleoresin was conducted in this study. Microencapsulation was done to maintain the active component present in the ginger essential oil and oleoresin. This study aims to determine the characteristics of the ginger essential oils microcapsules and pulp ginger oleoresins microcapsules. Ginger essential oil was taken in advance using distillation techniques. The extraction of pulps was done using ethanol 96% with variations in ratio of material: solvent are 1:4, 1:5, and 1:6 (w/v). Purification was done using a rotary vacuum evaporator. Essential oils and oleoresins are then microencapsulated by spray drying technique using feed rate of 15 ml/min and inlet temperature of 120 Â°C. Coating materials used are maltodextrin with a concentration of 5% (w/v). Variations in the ratio of essential oil weight or oleoresin weight:maltodextrin weight are 1:50, 1:25, and 1:16,7. The results showed that the highest oleoresin extraction yield was 6.97% (db). The highest microencapsulation efficiency of ginger essential oils was performed using the ratio of essential oils: maltodextrin = 1:25. These microcapsules have water content average of 6.7% (db), Î±w 0.25, bulk density 0.47 g/ml, solubility 556.67 seconds, total oil 28.39 x10-2oil g/gmicrocapsules, surface oil 9.12 x10-2g /g microcapsules, the microencapsulation efficiency was 17.43% and size estimates ranged from 1.39 to 11.10 Î¼m. The highest microencapsulation efficiency of pulp ginger oleoresin was reached by the ratio of pulp ginger oleoresin:maltodextrin = 1:16,7. These microcapsules have an average water content of 6.37% (db), Î±w 0.20, bulk density 0.46 g / ml, solubility 622.33 seconds, total oil 42.62x10-2g / g microcapsules, surface oil 18.12 x10-2g / g microcapsules, microencapsulation efficiency 22.13%, and size estimates ranged from 1.05 to 12.90 Î¼m. Both of ginger essential oil and pulp ginger oleoresin have differents GC- MS profile after drying process.